A Stochastic Model of Demand Forecasting for Technical Manpower Planning - Kwak, N. K.; Garrett, Walter A.; Barone, Sam (Management Science, 1977)
This paper presents a stochastic technique for short-term demand forecasting of manpower requirements for a particular functional skin group. The demand model is adaptable to any organization in which the demand for services from a skill group is derived from several projects or activities. Working from these multi-project demands for skill group services, Bayesian decision analysis is used to produce a composite forecast of total skill group manpower demand. Options in the model provide for selectively varying the number and level of detail of the multi-project demand curves. The output of the model is useful for further manpower planning.